2016
DOI: 10.1016/j.biopsych.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Cannabinoids on Human Cognition—A Systematic Review

Abstract: Cannabis use has been associated with impaired cognition during acute intoxication as well as in the unintoxicated state in long-term users. However, the evidence has been mixed and contested, and no systematic reviews of the literature on neuropsychological task-based measures of cognition have been conducted in an attempt to synthesize the findings. We systematically review the empirical research published in the past decade (from January 2004 to February 2015) on acute and chronic effects of cannabis and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
418
4
14

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 546 publications
(458 citation statements)
references
References 146 publications
(256 reference statements)
22
418
4
14
Order By: Relevance
“…Clinical and Practical Psychopharmacology driving simulation studies have consistently shown that cannabis dose-dependently impairs psychomotor skills 7,10 ; this lends support to the hypothesis that cannabis use is a specific risk factor for traffic accidents.…”
Section: E553 J Clin Psychiatry 77:5 May 2016mentioning
confidence: 60%
See 2 more Smart Citations
“…Clinical and Practical Psychopharmacology driving simulation studies have consistently shown that cannabis dose-dependently impairs psychomotor skills 7,10 ; this lends support to the hypothesis that cannabis use is a specific risk factor for traffic accidents.…”
Section: E553 J Clin Psychiatry 77:5 May 2016mentioning
confidence: 60%
“…Impairments continue to be demonstrable in several cognitive domains even after discontinuation of cannabis use. 7,12 Such impairments may represent reverse causality; that is, persons who have poorer cognitive functioning may be more vulnerable to cannabis use and abuse. Such impairments may also represent residual cannabis effects, or the effects of cannabis withdrawal.…”
Section: Long-term Risks Associated With Cannabis Usementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, residual effects may have masked the effect of genotype variation on learning task performance and novelty-seeking behavior in the cannabis-dependent group. A number of studies have shown acute and short-term effects of cannabis on various domains of cognition (reviewed in Broyd et al, (2015)), which further underscores the need for future research that could disentangle pre-existing, acute and residual cognitive deficit in cannabis-dependent populations.…”
Section: Discussionmentioning
confidence: 99%
“…El objetivo de esta revisión narrativa es revisar y discutir lo que ocasiona en el cerebro y sus consecuencias en la toma de decisiones y la inteligencia. Otras revisiones han mostrado que la atención, la memoria y la función psicomotora están afectadas en consumidores de mariguana (por ejemplo, ver Broyd, van Hell, Beale, Yücel, & Solowij, 2015), pero poco se ha revisado sobre los efectos del consumo y la toma de decisiones y la inteligencia.…”
Section: Sistema Endocannabinoideunclassified